The prevalence and characteristics of visceral autonomic symptoms among migraineurs: A population-based study. (May 2022) - Togha, Mansoureh; Martami, Fahimeh; Jafari, Elham; Ariyanfar, Shadi; Hashemi, Seyedeh Melika
Background: There is limited evidence about visceral autonomic symptoms in the different phases of migraine attack. We evaluated the prevalence of these symptoms in migraineurs before, during, and after headache attacks. In addition, the association between migraine characteristics and visceral autonomic symptoms was investigated. Methods: A total of 605 participants who met the entry criteria were enrolled prospectively in this cross-sectional study. Participants were 18–60 years old and met the ICHD-3 criteria for migraine with or without aura. Information on the migraine symptoms was gathered from all participants in face-to-face interviews. A structured questionnaire was used to evaluate the related symptoms before, during, and after attacks. Migraine features of frequency, duration, and severity were also assessed. Results: Considering all phases, the most commonly present visceral symptom was nausea (52.9%). About half of participants reported at least one visceral symptom before the onset of attacks. While, during and after attacks, 71% and 36% of participants reported such characteristics, respectively. Notably, the migraine headache in participants with visceral symptoms was longer during attacks compared to participants without them (24.4 ± 29.6 vs. 16.8 ± 19.8; P = 0.008). Additionally, subjects with positive visceral symptoms experienced more severe migraine attacks than participants without symptoms for both the premonitory (8 ± 1.7 vs. 7.6 ± 1.8; P = 0.02) and during-attack (8.01 ± 1.7 vs. 7.09 ± 1.9; P = 0.001) phases. Conclusion: This study demonstrated that visceral symptoms were common in migraine sufferers not only during attacks but also in the premonitory and postdrome phases. Positive visceral symptoms were also associated with more burdensome headache attacks. Therefore, recognizing the phenotypic presentation of associated symptoms of migraine, especially during the pre-attack phase, could aid in early implementation of optimal management.